Parametrically Sufficient Optimality Conditions for Multiobjective Fractional Subset Programming Relating to Generalized $(η, ρ, θ)$-Invexity of Higher Order (Journal of Informatics and Mathematical Sciences, 2013)
Inspired by the recent investigations, a general framework for a class of $(η, ρ,θ)$-invex $n$-set functions of higher order $r≥ 1$ is introduced, and then some optimality conditions for multiobjective fractional programming on the generalized $(η,ρ,θ)$-invexity are established. The obtained results are general in nature and unify various results on fractional subset programming in the literature.
Keywords: Generalized invexity of higher order; Multiobjective fractional programming; Fractional subset programming; Sufficient optimality conditions